Rekonstruksi Kelembagaan Ekonomi Dan Keuangan Syariah Dalam Menghadapi Isu Kontemporer Dan Tantangan Global - Erin Rismaya; Layaman; Aan Jaelani (Institute of Research and Community Service at Islamic University of Bunga Bangsa Cirebon, 2026)
The institutional reconstruction of Islamic economics and finance represents an urgent necessity amid continuously evolving global dynamics. This article aims to comprehensively analyze the institutional conditions of Islamic economics and finance, identify structural gaps impeding its growth, and formulate an institutional reconstruction model grounded in maqasid al-shariah that is relevant to contemporary challenges. This research employs a qualitative approach through systematic literature review and normative-philosophical analysis based on maqasid al-shariah. Data were gathered through a systematic review of internationally reputable journals, reports from international financial institutions, and current regulations within the global Islamic finance ecosystem. The findings reveal that Islamic financial institutions face five primary challenges: (1) regulatory fragmentation across jurisdictions, (2) gaps in Islamic financial literacy and inclusion, (3) weak technological infrastructure and digital finance adoption, (4) governance and Shariah accountability crises, and (5) insufficient integration of Islamic financial instruments into the global financial architecture. As a novelty contribution, this study proposes the Integrative Islamic Institutional Reconstruction Model (IIIRM), grounded in five pillars: regulatory harmonization, literacy strengthening, digital transformation, governance reform, and global integration. This model offers a holistic framework bridging normative Shariah perspectives with the realities of the contemporary global financial system.